2017
DOI: 10.7754/clin.lab.2016.161203
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Epidermal Growth Factor rs4444903 Influences Susceptibility to HCV-Related Liver Cirrhosis and Hepatocellular Carcinoma in a Chinese Han Population:

Abstract: The EGF rs4444903 GG genotype is associated with higher susceptibility to HCV-related LC and HCC in the Chinese Han population. Screening of host genetic polymorphisms might be helpful in designing effective and efficient LC and HCC surveillance programs for chronic HCV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The risk of development from chronic hepatitis C (CHC) to HCC involves a complex interplay between the viral and host genetic factors 3. Our previous study4 together with others’ have revealed that host gene polymorphisms may play important roles in the development and progression of HCV-related HCC.…”
Section: Introductionmentioning
confidence: 94%
“…The risk of development from chronic hepatitis C (CHC) to HCC involves a complex interplay between the viral and host genetic factors 3. Our previous study4 together with others’ have revealed that host gene polymorphisms may play important roles in the development and progression of HCV-related HCC.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies also suggested a possible role of MTHFR rs1801133 in HCC progression, but further research showed conflicting results. This includes two recent meta-analyses, one of which confirmed the association, while the other rejected it, with the exception of the Asian subpopulation [ 9 , 11 , 37 ]. Recently, Pineda-Tenor et al [ 38 ] reported that MTHFR rs1801133 polymorphism is associated with the progression of liver fibrosis in chronic hepatitis C. However, we found no association between the MTHFR polymorphism and susceptibility to ALC or HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Seven articles were grouped into two or three studies because they contain two or three sources of controls [15,21,22,26,27,31] or two ethnicities [17,18]. Finally, 18 articles [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] were included in this meta-analysis. The selection process for eligible studies was presented in Fig.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The functional variation (G to A) identified by Shahbazi et al at position 61 (rs4444903 -61A > G) of 5'-UTR in the EGF gene is associated with EGF up-expression and risk of malignant melanoma [13]. Recently, a host of studies have attached importance to evaluating whether EGF rs4444903 polymorphism affects the risk of HBV/ HCV, liver cirrhosis and HCC, but with conflicting findings [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Therefore, we conducted this meta-analysis to review the available evidence and investigate the effects of EGF rs4444903 polymorphism on HCC susceptibility in the overall population.…”
Section: Introductionmentioning
confidence: 99%